40 undergraduates, 500 school students explored the world of engineering in UMP - Siti Nurfarmy, Ibrahim (2018)
Some 500 school students from Kuantan and Pekan got to experience what it took to be an engineer during an event called ‘Engineering Day’ organised by Universiti Malaysia Pahang (UMP) Mechanical Engineering Professional Student Club (MECHAPRO) that was held at Pekan Campus on November 23, 2018.